2020
DOI: 10.1002/bem.22303
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Method for Fabricating Tissue‐Mimicking Materials With Designated Relative Permittivity and Conductivity at 128 MHz

Abstract: Artificial materials that can simultaneously mimic the relative permittivity and conductivity of various human tissues are usually used in medical applications. However, the method of precisely designing these materials with designated values of both relative permittivity and conductivity at 3 T MRI resonance frequency is lacking. In this study, a reliable method is established to determine the compositions of artificial dielectric materials with designated relative permittivity and conductivity at 128 MHz. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, whether the theoretical model is suitable for the study of the response law of rock electricity and relative permeability in tight sandstone gas reservoirs with complex pore-throat structures has not been verified experimentally. Based on the results of previous studies, we found that the formation factors and resistance increase coefficients are all functions of pore structure parameters in the process of tight sandstone multiphase flow.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, whether the theoretical model is suitable for the study of the response law of rock electricity and relative permeability in tight sandstone gas reservoirs with complex pore-throat structures has not been verified experimentally. Based on the results of previous studies, we found that the formation factors and resistance increase coefficients are all functions of pore structure parameters in the process of tight sandstone multiphase flow.…”
Section: Introductionmentioning
confidence: 70%
“…Irreducible water is negligible in the Poiseuille formula, but it is essential to calculate the resistivity parameters. This is because the irreducible water may not flow in a two-phase flow but can conduct electricity. The model provides theoretical support for the study of the relationship between rock electrical properties and relative permeability. However, whether the theoretical model is suitable for the study of the response law of rock electricity and relative permeability in tight sandstone gas reservoirs with complex pore-throat structures has not been verified experimentally.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To validate the accuracy of simulation, we conducted a phantom experiment. A skin phantom modeled as a single uniform layer because of the similar water content of epidermis and dermis was fabricated according to the recipe [30] . It was fabricated by dissolving 0.3 g of p-toluic acid and 15 ml of n-propanol with 51 g of gelatin and 285 ml of deionized water.…”
Section: Phantom Verificationmentioning
confidence: 99%